Answers

  • Brainly User
2015-10-24T13:17:18+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The two numbers: x and y
x + y = 5     ⇒    y = 5 - x

Representation:
x = first number
5 - x = second number

Sum of their cubes:
(x)³ + (5-x)³ = 35
x³ + 125 - 75x + 15x² - x³ = 35
x³ - x² + 15x² - 75x + 125 = 35
15x² - 75x + 125 = 35

Transform to Quadratic Equation form, ax² + bx + c = 0
15x²  - 75x + 125 - 35 = 0
15x² - 75x + 90 = 0

Factor out the GCF of each term: 15
15 ( x² - 5x + 6) = 0

Factor x² - 5x + 6:
(x - 2) (x - 3) = 0

x - 2 = 0
x = 2

x - 3 = 0
x = 3

The two positive numbers are 2 and 3

The sum of their squares:
Sum of their squares = (2)² + (3)² 
Sum of their squares = 4 + 9
Sum of their squares = 13

The sum of the squares of the 2 and 3 is 13.

To check:
Sum of the two positive numbers 2 and 3 is 5
2 + 3 = 5

Sum of the cubes of the two positive numbers 2 and 3 is 35.
(2)³ + (3)³ = 35
(2)(2)(2) + (3)(3)(3) = 35
8 + 27 = 35
35 = 35
0